2018
DOI: 10.1186/s12885-018-4317-6
|View full text |Cite
|
Sign up to set email alerts
|

CTHRC1 induces non-small cell lung cancer (NSCLC) invasion through upregulating MMP-7/MMP-9

Abstract: BackgroundThe strong invasive and metastatic nature of non-small cell lung cancer (NSCLC) leads to poor prognosis. Collagen triple helix repeat containing 1 (CTHRC1) is involved in cell migration, motility and invasion. The object of this study is to investigate the involvement of CTHRC1 in NSCLC invasion and metastasis.MethodsA proteomic analysis was performed to identify the different expression proteins between NSCLC and normal tissues. Cell lines stably express CTHRC1, MMP7, MMP9 were established. Invasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 46 publications
6
44
0
Order By: Relevance
“…CTHRC1 was as originally found as an extracellular matrix glycoprotein during the arterial injury-repair process [5], which has been shown to modulate vascular remodeling, osteoblastic bone formation and cell migration [6,20]. In addition, CTHRC1 serves as a prognostic factor involved in driving human tumor progression [21][22][23][24][25]. In accordance with this evidence, we observed that CTHRC1 mRNA and protein were dramatically upregulated in both clinical samples and BCa Arch Med Sci cells.…”
Section: Discussionsupporting
confidence: 80%
“…CTHRC1 was as originally found as an extracellular matrix glycoprotein during the arterial injury-repair process [5], which has been shown to modulate vascular remodeling, osteoblastic bone formation and cell migration [6,20]. In addition, CTHRC1 serves as a prognostic factor involved in driving human tumor progression [21][22][23][24][25]. In accordance with this evidence, we observed that CTHRC1 mRNA and protein were dramatically upregulated in both clinical samples and BCa Arch Med Sci cells.…”
Section: Discussionsupporting
confidence: 80%
“…50 Increased expression of MMP9 was associated with poorer outcomes in nasopharyngeal carcinoma patients 52 and together with increased expression of CTHCR1 and MMP7 , higher expression of MMP9 was associated with a lower survival rate after surgery in non-small cell lung cancer patients. 53 This known connection between CTHCR1 and MMP7/MMP9 is reflected in the current study, with significant upregulation of CTHRC1 in FP tumors accompanied by increased expression of MMP7 (log2FoldChange = 4.26, padj = 8.87×10 −9 ) and MMP9 (log2FoldChange = 4.24, padj = 4.05×10 −8 ) (supplementary table 1). Together this suggests that CTHRC1 may be a key oncogenic driver in FP.…”
Section: Discussionsupporting
confidence: 65%
“…The Kaplan-Meier analysis results showed that higher levels of MMP9, CSF1R, and PTPRC were related to shorter survival time of TGCT patients. MMP9 is a class of enzymes involved in the degradation of the extracellular matrix, which was up-regulated in tumor tissue samples of multi cancer [59][60][61], such as TGCT [62], breast cancer [63], lung cancer [64]. Moreover, MMP9 overexpression was significantly associated with poor survival of nasopharyngeal carcinoma [65] and glioblastoma [66].…”
Section: Ppimentioning
confidence: 99%